Exploring collaboration experiences at the society-science nexus in a food security project in Tanzania. Issue 3 (3rd April 2021) - Löhr, Katharina; Weinhardt, Michael; Bonatti, Michelle; Schütt, Juliane; Graef, Frieder; Sieber, Stefan
ABSTRACT: In the search for solutions to global challenges, the way scientific research is carried out is rapidly changing. Interdisciplinary approaches through collaborative research projects are replacing traditional approaches. As complex operational details, including stakeholder perspectives, are oft overlooked in these projects, conflict and failure are more likely. Analysing the conflict experience of stakeholders and project members in a transdisciplinary research project, this paper examines the science-society nexus. Using an international, transdisciplinary project, conflict drivers and levels of conflict are identified. Continuous communication and monitoring throughout a project's lifetime with internal conflict prevention and management measures are proposed to facilitate collaborations.